Case Study of the Mother-Child Interaction Reality During Online Learning in Covid-19 Pandemic: Case Study of the Mother-Child Interaction Reality During Online Learning in Covid-19 Pandemic - Annisa Ikhwanus; Ammi Salamah; Ananda Khairana; Megawati Simanjuntak; Yulina Eva Riany (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
This study aims to see how mother-daughter interactions during the COVID-19 pandemic are based on the mother's perspective. The research design used a qualitative research design. Examples in this study are two mothers with children of primary school age and one mother with children of junior high school age. The research was conducted from 5 to 11 March 2021 in three places, namely Jakarta, Banten, and Bandung. The research method is a case study. The results showed that the interaction between mother and child involves two main concepts of acceptance and conflict. They listen with pride, express, take special time, say good things, praise, understand, and friendship between mother and child. Conflict resolution is designated in the category that can resolve conflicts and trigger conflicts. Categories that can resolve conflict include active listening, appreciation, rules, discipline, trust, and time together. In comparison, conflict triggers include conflict, openness, criticism, and position. Covid-19 causes children to experience dependence on maternal violence, stress on children, and indications of verbal abuse from mothers, to mothers who experience stress when accompanying children to learn to be brave.